2000
DOI: 10.1080/02772240009358929
|View full text |Cite
|
Sign up to set email alerts
|

Chemical characterization of Tan‐Sui River sediment in North Taiwan

Abstract: Surface sediment samples from four downstream sites of Tan-Sui River in Taipei metropolitan area were collected from 1997 to 1999. The semivolatile organic pollutants present in the sediments were screened by GC/MSD. Several target compounds including sixteen polycyclic aromatic hydrocarbons (PAHs), seven chlorobenzenes, two phthalates and the total amount of C8-C32 aliphatic hydrocarbons were quantified. The concentration of the 16 PAHs ranges from 0.21 to 5.69 μg/g of which fluoranthene, pyrene and phenanthr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 16 publications
0
13
0
2
Order By: Relevance
“…Zero-valent iron can serve as the electron donor and was capable of efficiently removing PAH (Chang et al 2007b). Liu et al (2000) found PAH, DEHP, nonylphenol, and heavy metals in samples collected from various Taiwanese rivers and we therefore studied the effects of these pollutants on the anaerobic degradation of PAH in mangrove sediment. The data in Table 3 also show that PAH anaerobic degradation was inhibited by the addition of DEHP, nonylphenol, or heavy metals.…”
Section: Resultsmentioning
confidence: 99%
“…Zero-valent iron can serve as the electron donor and was capable of efficiently removing PAH (Chang et al 2007b). Liu et al (2000) found PAH, DEHP, nonylphenol, and heavy metals in samples collected from various Taiwanese rivers and we therefore studied the effects of these pollutants on the anaerobic degradation of PAH in mangrove sediment. The data in Table 3 also show that PAH anaerobic degradation was inhibited by the addition of DEHP, nonylphenol, or heavy metals.…”
Section: Resultsmentioning
confidence: 99%
“…These esters find their way into water bodies mainly through domestic, agricultural, and industrial effluent discharges, leaching from solid waste dumps and storm water runoffs (Cespedes et al 2006;Fatoki and Noma 2000;Liu et al 2000;Fatoki and Vernon 1990).…”
Section: Introductionmentioning
confidence: 99%
“…动植物或肉制品中检测出 [3] 。在台湾,PAEs 广泛的存 在于河水、底泥和土壤中 [4] ,并发现其累积在鱼体内 [5] 。 许多实验发现,PAEs 因水溶性(solubility)和降解 性低,且亲脂性(hydrophobicity)和吸附性高,可以在 陆地和水域环境的食物链中发生生物累积 [2] ,造成不 正常的性发育和降低生殖功能而干扰繁殖和族群大 小 [6][7][8][9] 。Autian 研究指出,当母体内累积过多浓度的 PAE 会造成男性胎儿雌性化现象 [10] 。动物毒性试验研 究发现,某些 PAEs 对鼠類和大部份哺乳动物具有肝 脏和肾脏毒害性 [11] ;PAEs 对鱼类(例如虹鳟、大西洋 鲑鱼等)具强烈之生物浓缩作用, 易累积至生物体内之 脂肪层,长期下来会造成水中生物遗传因子突变、生 物体畸形、生理异常等 [12,13] …”
unclassified
“…分钟;加入反转录酵素 ( 后,对生物体所造成的危害是不可忽视的 [12,13] 。台湾 许多的水域受到 PAEs 污染 [4] ,监测水域生态的完整 性,以观察并评估生物受到环境中化学物质影响的情 形是非常重要的。许多无脊椎动物毒性测试议定书常 规性地使用在监管毒性测试 [14] ,常见的水质指标生物 为底栖无脊椎动物,其与水域底泥及悬浮物质交互作 用,因而可以充分反应此生态系的污染情形,例如多 齿新米虾(Neocaridina denticulate) [19,20] [27,28] 。先前的研究显示,PAEs 会降低米虾和淡水长 脚大虾的免疫活性和增加易感性 [21,23] ;本研究证明 hc…”
unclassified